Oxidative Stability of Cooked Chicken Breast Burgers Obtained from Organic, Free-range and Conventionally Reared Animals - Lawlor, J.B.; Sheehan, E.M.; Delahunty, C.M.; Morrissey, P.A.; Kerry, J.P. (International Journal of Poultry Science, 2003)
The oxidative stability of cooked chicken breast burgers from chickens reared on organic (n=3), free-range (n=3), and conventional (n=3) diets was determined. α-Tocopherol and fatty acid concentrations were also determined. Organic, free-range and conventional chicken breasts were obtained from local retail outlets. Significant (P<0.05) differences in α-tocopherol concentrations were found between samples indicating that α-tocopherol concentrations were dependant on the individual source diet rather than whether the sample was of organic, free-range or conventional origin. Concentrations of fatty acids also appeared to be dependent on individual source diets. Compared with other samples, the three organic samples and one free-range sample had lower concentrations of monounsaturated and polyunsaturated fatty acids of n-3 and n-6 series. Burgers were manufactured, cooked and stored in a modified atmosphere (20% CO2: 80% N2), held at 4 oC under fluorescent light and oxidation monitored on days 1, 3, 5 and 7. Significant (P<0.05) differences were found in lipid oxidation (monitored by malondialdehyde thiobarbituric acid (MDA-TBA) values) between samples on days 1, 3, 5 and 7 of refrigerated storage. α-Tocopherol concentration and MDA-TBA values appeared to be related in most samples. In general, MDA-TBA values were in the following order throughout the selected storage period: organic>free-range>conventional. It was concluded that cooked breast burgers from broilers fed organic diets had a lower shelf-life (oxidative) stability compared with cooked breast burgers from broilers free-range and conventional diets. Stability, in the present work, appeared to be related more to α-tocopherol concentration than to fatty acids.